If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6q + -5 = 2q + 3 + -10q Reorder the terms: -5 + -6q = 2q + 3 + -10q Reorder the terms: -5 + -6q = 3 + 2q + -10q Combine like terms: 2q + -10q = -8q -5 + -6q = 3 + -8q Solving -5 + -6q = 3 + -8q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '8q' to each side of the equation. -5 + -6q + 8q = 3 + -8q + 8q Combine like terms: -6q + 8q = 2q -5 + 2q = 3 + -8q + 8q Combine like terms: -8q + 8q = 0 -5 + 2q = 3 + 0 -5 + 2q = 3 Add '5' to each side of the equation. -5 + 5 + 2q = 3 + 5 Combine like terms: -5 + 5 = 0 0 + 2q = 3 + 5 2q = 3 + 5 Combine like terms: 3 + 5 = 8 2q = 8 Divide each side by '2'. q = 4 Simplifying q = 4
| r+192=-8r+3 | | 5x^2+20=5 | | 5(3x+9y)= | | 6x-8x+2=3 | | 4xy/4x=8x^2/4x | | (2x-2)+(5x-13)=90 | | 92=4u+12 | | 2p=36 | | -4f+3=-4-3f | | x-2=-23 | | .33(.2x-1)+.35x=.05(3x+7)-1.44 | | 4xy=8x^2 | | 7d-13=-13+7d | | 3-5z+1=-3-6z | | j-60=-j-4 | | m=5/3x-2 | | m/-14-4 | | |5x+10|=15 | | 4x(y)/4x=0 | | 4xy/4x=0 | | 34+x=x-2 | | 3(2h+7)= | | 1-7w=-6w-9 | | 7b+3=6 | | 4x(y)/4x | | P+35=17 | | 2x-2=5x-13 | | 1-7w=6w-9 | | T+44=-t-6 | | 4xy/4x | | -6+6p=8+8p | | 11y+7w-8w-4y= |